Statistical Forecasting of Cereal Grain Used in Livestock and Fisheries Feed of Nepal - Poudel, Nabaraj; Pradhan, Bijay Lal; Dhakal, Bhojan; Devkota, Hare Ram; Panta, Shankar Raj; Pradhan, Ambira; Pandey, Luma Nidhi (International Journal of Operational Research/Nepal, 2025)
Cereal grains play a central role in Nepal’s food security, serving as major inputs for human consumption as well as livestock and fisheries feed systems. Rapid growth in livestock and aquaculture has intensified pressure on cereal supplies, raising concerns about the long-term balance between food and feed uses. This study examines trends, growth patterns, and future requirements of foodgrains in Nepal using annual time-series data on cereal production, human consumption, livestock feed, fisheries feed, and total foodgrain requirements. Data were obtained from official publications of the Government of Nepal for the period 2007–2022. The analysis employs descriptive statistics, growth rate analysis, correlation analysis, linear and log-linear trend models, and exponential smoothing (Holt) methods for short- to medium-term forecasting. Results indicate that total foodgrain production has increased steadily, but at a slower pace than aggregate demand driven mainly by livestock and rapidly expanding fisheries feed requirements. Feedgrain use in fisheries exhibits the highest compound annual growth rate, reflecting the dynamic expansion of aquaculture. Strong positive correlations are observed between livestock feed demand and total foodgrain requirement, while foodgrain use for human consumption shows a strong negative association with feed demand, highlighting growing competition between food and feed uses. Forecast comparisons suggest that simple trend-based and Holt exponential smoothing models provide reliable projections under limited data conditions, with the Holt model performing particularly well for fisheries feed demand. The findings underscore the need for an integrated food–feed policy framework in Nepal, emphasizing improvements in cereal productivity, feed efficiency, forage-based systems, and sustainable livestock and fisheries development to ensure long-term food and nutritional security.